COSIMA-Rosetta calibration for in situ characterization of 67P/Churyumov–Gerasimenko cometary inorganic compounds. (November 2015) - Krüger, Harald; Stephan, Thomas; Engrand, Cécile; Briois, Christelle; Siljeström, Sandra; Merouane, Sihane; Baklouti, Donia; Fischer, Henning; Fray, Nicolas; Hornung, Klaus; Lehto, Harry; Orthous-Daunay, Francois-Régis; et al.
Abstract: COmetary Secondary Ion Mass Analyzer (COSIMA) is a time-of-flight secondary ion mass spectrometry (TOF-SIMS) instrument on board the Rosetta space mission. COSIMA has been designed to measure the composition of cometary dust particles. It has a mass resolution m /Δ m of 1400 at mass 100 u, thus enabling the discrimination of inorganic mass peaks from organic ones in the mass spectra. We have evaluated the identification capabilities of the reference model of COSIMA for inorganic compounds using a suite of terrestrial minerals that are relevant for cometary science. Ground calibration demonstrated that the performances of the flight model were similar to that of the reference model. The list of minerals used in this study was chosen based on the mineralogy of meteorites, interplanetary dust particles and Stardust samples. It contains anhydrous and hydrous ferromagnesian silicates, refractory silicates and oxides (present in meteoritic Ca–Al-rich inclusions), carbonates, and Fe–Ni sulfides. From the analyses of these minerals, we have calculated relative sensitivity factors for a suite of major and minor elements in order to provide a basis for element quantification for the possible identification of major mineral classes present in the cometary particles. Highlights: Preparation for the analysis of dust particles from comet 67P/Churyumov–Gerasimenko. Calibration of inorganic species for the COSIMA dust analyzer on board Rosetta. Relative sensitivity factor for COSIMA mass spectra using terrestrial minerals.